Elementary linear algebra - Anton, Howard (Wiley, 1973)
Problem based introductory text. This text presents the fundamentals of linear algebra, addressing students' changing needs. It emphasises relationships between concepts, establishing the thread between systems of equations, matrices, determinants, vectors and other values. This text combines linear algebra theory with applications and addresses students' changing needs. It emphasises relationships between concepts, establishing the thread between systems of equations, matrices, determinants, vectors and other values. Noted for its expository style and clarity of presentation, the revision of this best-selling Linear Algebra text combines Linear Algebra theory with applications, and addresses a new generation of students' changing needs. Abstract: When it comes to learning linear algebra, engineers trust Anton. The tenth edition presents the key concepts and topics along with engaging and contemporary applications. The chapters have been reorganized to bring up some of the more abstract topics and make the material more accessible. More theoretical exercises at all levels of difficulty are integrated throughout the pages, including true/false questions that address conceptual ideas. New marginal notes provide a fuller explanation when new methods and complex logical steps are included in proofs. Small-scale applications also show how concepts are applied to help engineers develop their mathematical reasoning.